A case of envenoming by a Persian false-horned viper Pseudocerastes persicus (Duméril, Bibron & Duméril, 1854) (Serpentes: Viperidae) in Southeastern Iran. (February 2023) - Kazemi, Seyed Mahdi; Jahan-Mahin, Mohammad Hossein; Zangi, Bahman; Khozani, Reyhaneh Shams; Warrell, David A.
Abstract: Despite the wide distribution of the Persian false-horned viper ( Pseudocerastes persicus ) in the Middle East, few identified bites have been reported. A 33-year-old herpetologist bitten on the hand by Pseudocerastes persicus in Kerman Province, Southeastern Iran, developed local pain and extensive swelling with mild non-specific systemic symptoms and minimal laboratory evidence of systemic envenoming. Graphical abstract: Image 1 Highlights: Persian false-horned viper ( Pseudocerastes persicus ) widely distributed. No published well-documented cases of bites or envenoming. Herpetologist bitten Southeastern Iran. He developed local pain, swelling, minimal systemic envenoming. Treated with specific antivenom with full recovery.